Hiperbolizacja jako narzędzie politycznej manipulacji (na przykładzie nagłówków prasowych w tygodnikach „Do Rzeczy” i „W Sieci”) - Kujawiak, Aleksandra (Acta Universitatis Lodziensis. Folia Linguistica, 2018)
The article features the analysis of hyperbole as a means of political manipulation using an example of press headlines. The collected material was analyzed taking the value criterion into account. Negative and positive hyperboles and hyperbolization devices were distinguished which turned out to be mainly the lexemes included in specific semantic fields.